2003
DOI: 10.1114/1.1603257
|View full text |Cite
|
Sign up to set email alerts
|

Path-Dependent Hemodynamics of the Stenosed Carotid Bifurcation

Abstract: Previous work using computational simulations and experimental flow visualizations has demonstrated marked differences in local flow patterns between stenosed carotid bifurcation models having the same stenosis severity but different stenosis geometries. Since local blood flow patterns are known to influence thrombosis and atherosclerotic plaque development and rupture, such differences may in turn reflect differences in thromboembolic and atherosclerotic potential, and hence risk of ischemic stroke. Towards t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 46 publications
1
50
0
2
Order By: Relevance
“…bifurcation models demonstrated that there were differences between eccentric and concentric stenosis with respect to the size of the poststenotic recirculation zone, as well as the severity and distribution of wall shear stress. 5 Using the models, the deposition of platelet and monocyte-sized particles on the vessel wall was more distinct proximal to the eccentric stenosis than proximal to the concentric stenosis. 25 This suggests that eccentric stenosis is more prone to platelet activation and aggregation due to attenuated platelet deposition and plaque growth, as well as rupture due to attenuated monocyte deposition.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…bifurcation models demonstrated that there were differences between eccentric and concentric stenosis with respect to the size of the poststenotic recirculation zone, as well as the severity and distribution of wall shear stress. 5 Using the models, the deposition of platelet and monocyte-sized particles on the vessel wall was more distinct proximal to the eccentric stenosis than proximal to the concentric stenosis. 25 This suggests that eccentric stenosis is more prone to platelet activation and aggregation due to attenuated platelet deposition and plaque growth, as well as rupture due to attenuated monocyte deposition.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3][4] However, because most patients with carotid stenosis without surgical revascularization are free from occurrence or recurrence of ischemic cerebrovascular events after many years, the use of stenosis severity as a measure of stroke risk has a relatively poor specificity. 5 Thus, additional indicators are needed to identify carotid artery lesions associated with a higher risk of stroke. The vulnerability of the carotid plaque morphology has been recognized as an important predictor for stroke.…”
mentioning
confidence: 99%
“…Previous studies of biomechanical platelet activation have typically modeled platelets as either infinitesimal [22,23,25,[31][32][33] or finite-sized [26,[34][35][36][37][38] particles. In either case, Lagrangian particle tracking of the position and stress histories of individual platelet surrogates in the flow is used.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially important in assessing blood damage as surface shear stress and exposure time (related to particle trajectory) have been used as primary factors for quantifying blood damage in previous studies. 10,14,27 The objective of the current study is to model the particulate flow fields in the hinge region of three aortic BMHVs during the leakage mid-diastole flow phase with high spatiotemporal resolution and numerically compute the platelet shear damage induced by each hinge design. Using a particle-based method 3 with fully-coupled fluid-solid interaction, platelet damage incurred in hinge flows is studied by releasing geometrically accurate 3D platelets with meshed surfaces in the hinge flow and computing surface shear stresses experienced by these platelets.…”
Section: Introductionmentioning
confidence: 99%